THE IMPLEMENTATION OF TEACHING SPEAKING BY USING STORY TELLING TECHNIQUE AT FAJAR COURSE PARE KEDIRI - Isnan, Achmad (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2025)
This research aimed to explore how storytelling is implemented in teaching speaking at FAJAR English Course in Pare, Kediri. The study used a descriptive qualitative method to describe the real teaching process without manipulating any variables. Data were collected through observation, interviews, and documentation, focusing on the teacher’s preparation, materials, media, methods, evaluation, and student responses. The results showed that the teacher prepared lessons with a clear syllabus and lesson plan; used meaningful stories with moral values taken from books, family traditions, and online sources; and applied engaging media like dolls, drawing cards, and even monopoly games. Storytelling was used as the main method, encouraging students to summarize or create their own stories to share in class. Evaluation was conducted through weekly performance assessments, followed by discussion and support in additional sessions. Students responded enthusiastically and participated actively, showing that storytelling not only builds their speaking fluency. boosts their confidence and motivation in a fun, non-formal learning environment, but also develop their English speaking skills.